Lipid-based colloidal carriers for topical application of antiviral drugs - Lopes, Carla M. (2018)
Herpes infections are very frequent infectious diseases, especially in individuals whose immune system is weakened, causing manifestations in the central nervous system that leave severe squeals in about 80% of cases. There are several types of etiologic agents of herpes infections, being the most well-known the Herpes Simplex Virus HSV 1 and 2. HSV 1 usually affects the face, lips, gums, palate, tongue and nasal mucosa and can spread to other parts of the body and HSV 2 reaches the genital area, affecting both men and women. The most common current therapies to treat herpes infections are based on topical formulations containing an antiviral agent, but whose effectiveness is limited due to low skin penetration of the active agent, requiring the application of about four or up to five times per day for improving the therapeutic effectiveness of the formulation. For this reason, the development of topical formulations containing lipid based colloidal carriers is a promising approach to promote more effective penetration through the skin and thus to reduce the frequency of application. This chapter provides an overview of the current lipid-based colloidal carriers developed for topical application of antiviral drugs, and summarizes the most important challenges and strategies that researchers will find when developing formulations with this purpose.